Business History and trading firms in Colonial Multan: A Historical Review - Chuadhary, Abida Kausar; Iqbal, Muahmmad (Journal of Development and Social Sciences, 2025)
The aim of this article is to develop a general narrative of firms and cottage industries and their connected zones that led the growth of import and export in the 19th century British Multan and thus to supply missing chain of Business History. The trading companies associated with import and export had several features in common with trading firms globally, especially a high degree of mobility, institutional adaptations and occasionally diversification into banking and manufacturing Sector. But the certain aspects to be heighted of process with in the regions where they operated: such as the differences between the ports and the inland trading orders between cities and indigenous firms. This research will try show how the town of Multan emerged as the main trading center during the British period. For example, the canal colonies had deprived Multan for export trade in wheat with the competition of Lyallpur. The development of lower Bari Doab Colony had shifted the centre of gravity of the cotton industry from Multan to newly developed colony towns of Jahanian, Kahanawal and Mianchannu to with the large supply of American cotton. The direct route to Karachi by Khanawal Lodhran chord lines serves further to increase the industrial importance of these mandies and cargo to Multan. Official and non-Official records from British Indian Library London and civil secretariat Lahore are being consulted to draw empirical results.